2017
DOI: 10.1016/j.adolescence.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of school dropout and absenteeism among adolescent girls from marginalized community in north Karnataka, south India

Abstract: Secondary education among lower caste adolescent girls living in rural Karnataka, South India, is characterized by high rates of school drop-out and absenteeism. A cross-sectional baseline survey (N=2275) was conducted in 2014 as part of a cluster-randomized control trial among adolescent girls (13-14 year) and their families from marginalized communities in two districts of north Karnataka. Bivariate and multivariate logistic regression models were used. Overall, 8.7% girls reported secondary school dropout a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 31 publications
(45 reference statements)
2
56
0
2
Order By: Relevance
“…Consistent with other literatures, this research found a positive association between bullied adolescents and absenteeism which was due to unsafe feeling and truancy than non-bullied [37,38].…”
Section: Mental Health Behaviorssupporting
confidence: 91%
“…Consistent with other literatures, this research found a positive association between bullied adolescents and absenteeism which was due to unsafe feeling and truancy than non-bullied [37,38].…”
Section: Mental Health Behaviorssupporting
confidence: 91%
“…Given our research focus on the Parivartan program for adolescent boys, we were not able to carefully attend to the realities and experiences of adolescent girls. However, within the context of the larger Samata project, research on adolescent girls' secondary school dropout and retention have been conducted extensively (Beattie et al, ; Bhagavatheeswaran et al, ; Prakash et al, ; Ramanaik et al, ). While our data provide important information on emerging dynamics of masculinity, some areas may have been under‐explored as the short duration of our fieldwork did not allow us to fully describe the diverse experiences and realities of adolescent schoolboys.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have resulted in school attendance and attrition rate problems among girls [7]. Higher attrition in high school level education (13-16 years), especially for girls, where gendered social and school experiences combined with financial, marital and childbearing roles, to discourage teenage girls' contribution [8]. A student's family poverty level and the neighborhood poverty level affect student attrition behavior [9].…”
Section: Introductionmentioning
confidence: 99%